3D FE model of frictional heating and wear with a mutual influence of the sliding velocity and temperature in a disc brake. (March 2015) - Yevtushenko, A.A.; Grzes, P.
Abstract: Numerical simulation of frictional heating in a disc brake of a typical passenger vehicle based on the equation of motion and the boundary-value problem of heat conduction was carried out. An influence of temperature-dependent coefficient of friction on the sliding velocity, braking time, braking distance and the thermomechanical wear was studied. Two materials of the pad combined with the cast-iron brake disc were examined. The dependencies of the coefficient of friction and wear rate on the temperature and contact pressure were derived from experimental measurements and implemented to the computational model of the brake. Comparisons of temperature for validation purposes calculated using the contact model developed in this study were made with the model introducing an approach based on the heat partition adopted from other studies.